Psychology of Morality and Values in Secondary Schools - Karimov, Eldar (Scholarya Demo Journal of Ruby, 2018)
Teaching morality and values is of particular importance in all societies and cultures. Despite the fact that everyone recognizes the importance of this problem, very few people follow the rules of psychological development. On one hand, our study aims to elucidate the peculiarities of the children’s development and adolescence; on the other hand, it shows the basics of teaching morality and values in accordance with these features. The study provides information on the relationship between morality and values, the psychological foundation of these two concepts and methods of teaching these moral principles, which occupy an important place in human life. In addition, it shows the difference between the former and the modern method in teaching morality and values, as well as the negative or positive influence of these methods on individuals. The study also paid special attention to the opinions of researchers, who are well known in the field of moral standards and child psychology. Ultimately, in today’s schools, morality and values should be taught taking into account the psychological state of children, and the psychological consequences that affect their future life. The purpose of this work is to study in depth the psychology morality and values in secondary schools and to put forward useful information by exploring various literatures on this topic.